Congenital bile duct cyst (BDC) is a more indolent disease in children compared to adults, except for Todani type IV-A BDC: results of the European multicenter study of the French Surgical Association. Issue 6 (June 2016) - Ouaissi, Mehdi; Kianmanesh, Reza; Ragot, Emilia; Belghiti, Jacques; Wildhaber, Barbara; Nuzzo, Gennaro; Dubois, Remi; Revillon, Yann; Cherqui, Daniel; Azoulay, Daniel; Letoublon, Chritian; Pruvot, François-René; et al.
Abstract: Aim: To compare clinical presentation, operative management and short- and long-term outcomes of congenital bile duct cysts (BDC) in adults with children. Methods: Retrospective multi-institutional Association Francaise de Chirurgie study of Todani types I+IVB and IVA BDC. Results: During the 37-year period to 2011, 33 centers included 314 patients (98 children; 216 adults). The adult population included more high-risk patients, with more active, more frequent prior treatment (47.7% vs 11.2%; p < 0.0001), more complicated presentation (50.5% vs 35.7%; p = 0.015), more synchronous biliary cancer (11.6% vs 0%; p = 0.0118) and more major surgery (23.6% vs 2%; p < 0.0001), but this latter feature was only true for type I+IVB BDC. Compared to children, the postoperative morbidity (48.1% vs 20.4%; p < 0.0001), the need for repeat procedures and the status at follow-up were worse in adults (27% vs 8.8%; p = 0.0009). However, severe postoperative morbidity and fair or poor status at follow-up were not statistically different for type IVA BDC, irrespective of patients' age. Synchronous cancer, prior HBP surgery and Todani type IVA BDC were independent predictive factors of poor or fair long-term outcome. Conclusion: BDC is a more indolent disease in children compared to adults, except for Todani type IV-A BDC.